Fault distance calculation considering sequence impedance values on the distribution network - J. Awalin, Lilik; Syahirah, Abdul Halim; Nor Azuana, Ramli (AIP Publishing, 2023)
Fault on distribution line needs to be stored as quickly as possible. It is due to fault effect to the damage of equipment and blackout. In this paper, single line to ground fault is considered in the simulation. The fault distance calculation is used an impedance-based method. The value of negative and positive sequence impedance was utilized in the formulation. The various distances in each section are simulated in order to observe the accuracy of the impedance-based method. The test network was adopted from the real data from Tenaga Nasional Berhad (TNB) Malaysia. The network was installed as an underground distribution network with 19 nodes (branches and main feeder). The obtained result shows that by considering sequence impedance to the fault distance calculation, it is able to generate acceptable accuracy.